2022
DOI: 10.1128/jvi.02024-21
|View full text |Cite
|
Sign up to set email alerts
|

Birnaviridae Virus Factories Show Features of Liquid-Liquid Phase Separation and Are Distinct from Paracrystalline Arrays of Virions Observed by Electron Microscopy

Abstract: To gain more information about the nature of Birnaviridae virus factories (VFs), we used a recombinant infectious bursal disease virus (IBDV) expressing split-GFP11 tagged to the polymerase (VP1) that we have previously shown is a marker for VFs in infected cells expressing GFP1-10. We found that VFs co-localized with 5-ethynyl uridine in the presence of actinomycin, demonstrating they contained newly synthesized viral RNA, and VFs were visible in infected cells that were fixed and perm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…In light of our results, it is conceivable to hypothesize that viral interaction with the EE membranes acts as a first step in the RCs biogenesis, leading to the growth of biomolecular condensates with LLPS characteristics around EE membranes, as recently proposed (Brodrick and Broadbent, 2023). In support of this model, both the RNA dependent RNA polymerase VP1 and the viral dsRNA associate to endosomes (6) and to the LLPS condensates (Delgui et al, 2013; Reddy et al, 2022). Further experiments are needed in order to link the association of VP3 to EE membranes with biomolecular condensate formation.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In light of our results, it is conceivable to hypothesize that viral interaction with the EE membranes acts as a first step in the RCs biogenesis, leading to the growth of biomolecular condensates with LLPS characteristics around EE membranes, as recently proposed (Brodrick and Broadbent, 2023). In support of this model, both the RNA dependent RNA polymerase VP1 and the viral dsRNA associate to endosomes (6) and to the LLPS condensates (Delgui et al, 2013; Reddy et al, 2022). Further experiments are needed in order to link the association of VP3 to EE membranes with biomolecular condensate formation.…”
Section: Discussionmentioning
confidence: 84%
“…It has recently been reported that the RCs of IBDV exhibit liquid-liquid phase separation (LLPS) (Reddy et al, 2022). In LLPS, one or more biomolecules form a network of mild homo- and heterotypic interactions, resulting in the formation of a distinct liquid phase within a liquid medium (Banani et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Considering these methodology limits, we have been working on setting up the correlative light and electron microscopy (CLEM) platform, which has been widely performed recently in many LLPS investigations to confirm the phase separation property of candidate proteins in vivo . 76 , 77 , 78 It might be a powerful and effective tool to explore Aurora-A LLPS in depth.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, STARSS measurements demonstrated the tendency of the Gag-homologous protein Arc to oligomerize even in crowded subcellular regions not measurable with conventional FCS due to the difficulties in detection of signal fluctuations. Considering the tendency of Arc to oligomerize and bind RNAs, it is tempting to speculate that these regions might represent liquid–liquid-phase-separated condensates resulting from the high density of proteins and RNAs, in analogy to viral factories 32 , 33 .…”
Section: Discussionmentioning
confidence: 99%